Design, development, and drying kinetics of infrared‐assisted hot air dryer for turmeric slices. (10th October 2021) - Jeevarathinam, G.; Pandiselvam, R.; Pandiarajan, T.; Preetha, P.; Krishnakumar, T.; Balakrishnan, M.; Thirupathi, V.; Ganapathy, S.; Amirtham, D.
Abstract: An infrared‐assisted hot air dryer was designed and developed for turmeric slices. The dryer has been developed using an infrared heating source, heating coils, and blower. The total power required for the infrared drying and hot air drying was 2.25 kW and 36.35 kWh, respectively, with a blower capacity of 6.06 m 3 /min. An infrared drying (IRD), hot air drying (HAD), and infrared‐assisted hot air drying (IRHAD) were used to dry turmeric slices (5 mm thickness) at different drying temperatures 50°C, 60°C, and 70°C with constant air velocity 2 m/s and bed thickness 25 mm. The maximum drying efficiency of 25.22% and the minimum specific energy consumption of 1.24 kWh/kg were observed in the IRHAD method at 70°C and considered as the best drying method for drying turmeric slices. The drying rates values were double in IRHAD than IRD and HAD. Seven drying models, namely, Newton, Page, Modified page, Diffusion approximation, Two‐term exponential, Henderson–Pabis, and Logarithmic, were used to validate the experimental data obtained during drying. Based on the maximum R 2 value and lowest error values, the Page model was found to be the best fit for characterizing the drying kinetics of turmeric slices. At 60°C drying temperature, the logarithmic model and two‐term exponential model were found best fit for HAD and IRHAD, respectively. Practical Applications: Recently, turmeric gaining a lot of economic importance due to its antiviral properties and health benefits. Turmeric has many applications in the food industry, including natural coloring agents, flavor enhancers, and preservatives. Washing, boiling, drying, polishing, and size reduction are the unit operations involved during the processing of turmeric. The commercial value of turmeric can be decided based on the percentage of volatile compounds present. Many studies observed that the reduction in volatile compounds due to improper drying. The farmers following the sun drying techniques, which consume more time, non‐homogenous drying, and lesser drying rate. Hence, an efficient alternate drying technique should be identified to overcome the problems faced by the farmers and turmeric processing industries. In this context, the present study was undertaken to design an infrared‐assisted dryer for efficient, quick, and uniform heating of turmeric slices. Abstract :